Pulse Oximeter Monitoring Bracelet for COVID-19 Patient using Seeeduino - Suhartina, Rahmalisa; Abuzairi, Tomy (Universitas Ahmad Dahlan, 2021)
The increase in positive cases of COVID-19 makes it grave to monitor the level of oxygen saturation in the blood (SPO2) of COVID-19 patients. The purpose is to prevent silent hypoxia, which lowers oxygen levels in the blood without symptoms. In general, a conventional pulse oximeter is a clip that is clamped on a finger to measure SPO2 levels and heart rate per minute (HR). This research aims to design a compact pulse oximeter monitoring bracelet. The main components of the pulse oximeter monitoring bracelet are the Seeeduino XIAO microcontroller, MAX30100 sensor, and OLED display. The method of collecting data on ten people using a conventional pulse oximeter and prototype device to measure SPO2 and HR levels the interval 30 seconds were a taken measurement. The results show that the Pearson correlation value for SPO2 and HR are -0.73 and 0.98, respectively. These results demonstrated that there is a strong relationship between variables and sufficient linearity. In addition, a pulse oximeter monitoring bracelet is easy to use and low-costs, which makes it an attractive option for the successful implementation of such monitoring SPO2 and HR of COVID-19 patients.